Game of chance elements in free-to-play mobile games. A freemium business model monetization tool in need of self-regulation? - Marco Josef Koeder; Ema Tanaka (International Telecommunications Society (ITS), 2017)
This paper conceptualizes “Gacha”, a lottery mechanism to win virtual items, which was developed in Japan, as game of chance elements in mobile games which is used for monetization in freemium business models. Based on the concept of Gacha, referring to previous studies, this paper also analyzes the difference of mobile game regulation between the West and Japan. Japan has a longer history and more experience in both monetization of mobile games with gambling like elements (Gacha) and its regulation including self-regulation. Specific kinds of Gacha are regulated in Japan, not because of its quasi-gamble mechanism, which is in contrast to previous study perception, but because of its misleading marketing promotion method. The Japanese regulatory approach to handle the game of chance issues is to increase the transparency of probability of winning which gives consumer better chances to consider their total amount of spending on Gacha.
Keywords: 330; Free-to-play; freemium; mobile games; behavior; regulation; Gambling; virtual goods; Japan; Europe